Peripheral vision in basketball players at different level of experience - Chaliburda, A.; Markwell, L.; Wolosz, P.; Sadowski, J. (Polish Journal of Sport and Tourism, 2023)
Introduction. This study focuses on the sensory information delivered by the visual system, particularly in the peripheral visual field (PVF). Visual abilities, especially the ability to detect peripheral information, have been identified as important factors for successful performance in team sports. Athletes often need to divide their visual focus between central and peripheral fields to achieve optimal performance. However, research on visual perception in athletes with varying levels of experience is still limited. The aim of the study was to compare peripheral perception of basketball players at different level of experience.